Sorbitol-Oleat Poliester: Produksi, Sifat Fisikokimia, dan Perubahannya selama Penggorenggan - Agnes Murdiati; Hastari Wuryastuti; Y. Marsono; Eni Harmayani (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2009)
Excess intake of fat and oil resulted in various problem of health disorder. In order to reduce the intake of fat, fat re- placer sorbitol-oleic polyester (SOPE) was developed, by method of esterification methyl oleic and sorbitol at 150 oC for 8 hours. The objectives of this research were to evaluate the characteristics of SOPE produced and the character- istics change in frying. The result showed that SOPE had the color of yellowish brown (y=5 r=0.9 b=0.3 of Lovibond scale), viscosity of 4 cP, refractive index at 25 oC of 1.4307, hydroxyl value of 16.53 mg KOH/g, smoke point of 115 oC, acid value of 2.22 mg KOH/g, and yield of 77.5 %. During frying, the appearance of SOPE became darker, acid value and hydroxyl value was increased by constant rate of 0.37 mg KOH/g/day and 1.38 mg KOH/g/day respectively, and peroxide value increased in the early period and then decreased again, small decreased in smoked point while viscosity of SOPE did not change significantly.ABSTRAKAsupan lemak yang berlebih mengakibatkan berbagai gangguan kesehatan. Untuk mengurangi asupan lemak dibuat senyawa pengganti lemak (fat replacer) sorbitol-oleat poliester (SOPE). Dalam penelitian ini SOPE diproduksi secara kimia dari sorbitol dan asam oleat melalui reaksi esterifikasi antara metil oleat dengan sorbitol pada suhu 150 oC se- lama 8 jam, di dalam suatu reaktor logam. Hasil yang diperoleh menunjukkan bahwa SOPE yang dihasilkan berwarna kuning kecoklatan (k=5 m=0,9 b=0,3 skala Lovibond), viskositas 4 cP, indeks refraksi pada 25 oC sebesar 1,4307, angka hidroksil 16,53 mg KOH/g SOPE, angka asam 2,22 mg KOH/g SOPE, dan yield 77,5 %. Selama penggorengan, SOPE mengalami peningkatan intensitas warna coklat, peningkatan angka asam dengan konstanta kecepatan 0,39 mg KOH/gSOPE/hari, peningkatan angka hidroksil dengan konstanta kecepatan 1,26 mg KOH/gSOPE/hari, kenaikan angka peroksida pada awal pemanasan yang selanjutnya mengalami penurunan kembali, penurunan sedikit titik asap, dan tidak terjadi perubahan viskositas.